An Early Ordovician fossil seamount of the Hongguleleng–Balkybey Ocean in the northern West Junggar terrane (NW China) and its implications for the ocean evolution. (1st June 2020) - Yang, Yaqi; Zhao, Lei; Zheng, Rongguo; Xu, Qinqin; Liu, Jianhua; Zhang, Jin
Graphical abstract: Highlights: A "typical" seamount rock assemblage is determined in the northern West Junggar terrane, NW China. The fossil seamount formed in the Early Ordovician. The seamount formed in an ocean intraplate environment and derived from a mantle plume source. Abstract: Seamounts are common constituents in the ocean basins today, and can be accreted in the accretionary prism or carried into the subduction zone together with the slab. Here, we report a typical rock assemblage of a fossil seamount in the northern West Junggar terrane (NW China), which is composed of ocean island basalt (OIB), marble, siliceous mudstone, and chert. The OIB yields a zircon SHRIMP U–Pb age of 475 ± 4 Ma, and the detrital zircons of siliceous mudstone give a weighted average age of 472 ± 2 Ma (n = 50, MSWD = 1.09), showing the fossil seamount formed in the Early Ordovician. Geochemically, all the basalt samples manifest as high concentrations of TiO2 (mostly within 1.51–3.22 wt%), Na2 O + K2 O (4.6–10.65 wt%), and high εNd(t) values (+3.01–+3.65), with LREE enrichment ((La/Yb)N  = 11–20.6) and no Nb, Ta negative anomalies, which suggests the signature of OIB. Moreover, the OIBs are inferred to have originated from a plume-related mantle source and to have been produced by ca. 1%–3% garnet + spinel lherzolite partial melting in an oceanic intraplate setting. The seamount from the Hebukesaier ophiolitic mélange (HOM) is suggested to have accreted in the accretionary complex with oceanic fragments during the Middle–Late Ordovician.